Secretory lysosomes of mouse mast cells store and exocytose active caspase‐3 in a strictly granzyme B dependent manner. (December 2013) - Zorn, Carolin N.; Pardo, Julian; Martin, Praxedis; Kuhny, Marcel; Simon, Markus M.; Huber, Michael
<x xml:space="preserve">Abstract</x> In this study, we report that cytoplasmic granules from in vivo and in vitro derived mouse mast cells (MCs) contain active granzyme B (gzmB) and caspase‐3, which is consistent with recent findings. Studying WT and gzmB‐deficient mice, we observed that BM‐derived MCs (BMMCs) from both strains contain cytosolic pro‐caspase‐3, but only WT BMMCs expressed active caspase‐3 limited to their secretory lysosomes. Confocal microscopy revealed colocalization of active caspase‐3 and gzmB in these cytoplasmic granules. The combined data demonstrate that the generation and storage of active caspase‐3 is gzmB‐dependent. The finding that BMMCs secrete caspase‐3 and gzmB after Ag stimulation suggests that both proteases contribute to extracellular MC‐mediated proteolytic events. Although the extracellular function of MC‐derived caspase‐3 remains unclear, we show that BMMC‐secreted caspase‐3 cleaves IL‐33, a cytokine that contributes to the development of asthma and arthritis. We also show that an in vitro propagated cytolytic T‐lymphocyte line constitutively expresses gzmB together with active caspase‐3, suggesting a novel interaction of these proteases in the execution of multiple innate and adaptive immune responses.